1996
DOI: 10.1007/s0021663540874
|View full text |Cite
|
Sign up to set email alerts
|

The determination of local structural units in amorphous SiBN 3 C by means of X-ray photoelectron and X-ray absorption spectroscopy

Abstract: X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES) spectroscopy at the K-edge of Si, N, and B are presented as techniques suited to determine structural units in amorphous SiBN(3)C. The measurements reported give evidence for the presence of tetrahedral (SiN(4))- and planar (BN(3))-groups. It is concluded that these structural elements dominate the atomic surroundings of B and Si, respectively. From the spectroscopic results we conclude that C is mainly bonded to N and is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
2
Order By: Relevance
“…The B K-edge XANES spectra of Si 3 B 3 N 7 , cubic BN (c-BN), and hexagonal BN (h-BN) are shown in Figure 3 a. [38,39] While the spectrum of h-BN is dominated by a strong 1s!p* resonance at 191.8 eVand a doublet at 198 eV (1s!s* resonances), in the spectrum of c-BN, the 1s!p* Figure 3. a) B K-edge XANES spectra of Si 3 B 3 N 7 , c-BN, and h-BN.…”
Section: Short-range Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…The B K-edge XANES spectra of Si 3 B 3 N 7 , cubic BN (c-BN), and hexagonal BN (h-BN) are shown in Figure 3 a. [38,39] While the spectrum of h-BN is dominated by a strong 1s!p* resonance at 191.8 eVand a doublet at 198 eV (1s!s* resonances), in the spectrum of c-BN, the 1s!p* Figure 3. a) B K-edge XANES spectra of Si 3 B 3 N 7 , c-BN, and h-BN.…”
Section: Short-range Ordermentioning
confidence: 99%
“…a) B K-edge XANES spectra of Si 3 B 3 N 7 , c-BN, and h-BN. [38,39] b) Si K-edge XANES spectra of Si 3 B 3 N 7 , a-Si 3 N 4 , and b-Si 3 N 4 . [40] c) N K-edge XANES spectra of Si 3 B 3 N 7 , a-Si 3 N 4 , and h-BN.…”
Section: Short-range Ordermentioning
confidence: 99%
“…While the short range order in the ceramics Si 3 B 3 N 7 and SiBN 3 C has been studied successfully using standard MAS NMR techniques ( 29 Si, 11 B, 15 N), 15,16 XANES spectroscopy 17,18 and X-ray and neutron diffraction techniques, 19 revealing BN 3 and SiN 4 units as the polyhedra constituting the network, the ordering on a scale down to 9 A Ê has been accessed by means of energy ®ltered transmission electron spectroscopy (EFTEM) and electron spectroscopic imaging (ESI). 20 These studies found that the ceramics Si 3 B 3 N 7 and SiBN 3 C are homogeneous with respect to the elemental distribution on a sub-nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…Die Aufklärung der kurzreichweitigen Ordnung in Si 3 B 3 N 7 erfolgte unter Verwendung von XANES, Streumethoden und Festkörper‐NMR‐Spektroskopie. In Abbildung 3 a ist das B‐K‐XANES‐Spektrum für die Titelverbindung den entsprechenden Spektren für hexagonales (h‐BN) und kubisches Bornitrid (c‐BN) gegenübergestellt 38. 39 Während das Spektrum von h‐BN von einer starken 1s→π*‐Resonanz bei 191.8 eV und einem Dublett um 198 eV (1s→σ*‐Resonanzen) dominiert wird, fehlt die 1s→π*‐Resonanz im Spektrum von c‐BN.…”
Section: Experimentelle Ansätze Zur Bestimmung Charakteristischer unclassified
“… a) B‐K‐XANES‐Spektren von Si 3 B 3 N 7 , h‐BN und c‐BN;38, 39 b) Si‐K‐XANES‐Spektren von Si 3 B 3 N 7 , α‐Si 3 N 4 und β‐Si 3 N 4 ;40 c) N‐K‐XANES‐Spektrum von Si 3 B 3 N 7 , α‐Si 3 N 4 und h‐BN. …”
Section: Experimentelle Ansätze Zur Bestimmung Charakteristischer unclassified